Model of State Management of Petroleum Sector – Case of Norway - Dośpiał-Borysiak, Katarzyna (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
The aim of the article is to discuss the Norwegian Model of hydrocarbon management and its impact on building a just and equal society. Since 1972, the model has been based on the separation of policy, commercial, and regulatory functions. Within each area there is state-controlled institution with its own distinct role. This model of separation of duties is however combined with other unique features which cannot be easily copied by other counties. These include a long tradition and high level of democratic co-operation, intergovernmental checks and balances, socio-democratic traditions of strong public involvement, mature institutional capacity (mainly a competent bureaucracy) and highly developed model of co-operation between government, business and research institutions.